1991
DOI: 10.1007/bf00012041
|View full text |Cite
|
Sign up to set email alerts
|

VA-mycorrhizae and mycorrhiza stimulating isoflavonoid compounds reduce plant herbicide injury

Abstract: Imazaquin, imazethapyr and pendimethalin showed high toxicity to sorghum plants grown in a greenhouse soil mix. However, mycorrhizal sorghum plants were less affected by herbicide toxicity than non-mycorrhizal ones, at low to moderate herbicide concentrations. VAM herbicide safening effects were more evident on imazaquin-treated plants, than for those treated with the other two herbicides. Applications of imazethapyr and pendimethalin at the two highest concentrations, but not imazaquin, reduced VAM colonizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
10

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 34 publications
(32 reference statements)
1
10
0
10
Order By: Relevance
“…The mechanisms by which flavonoid compounds stimulate fungal growth (Nair et al, 1991;Gianinazzi-Pearson et al, 1989) and root colonization (as reported here) cannot be determined from our experiments. As indicated by others (Adesanya, O'Neill & Roberts, 1986), the effects of these compounds on fungi may result from their effects on membrane permeability, enzyme activity or DNA transcription.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The mechanisms by which flavonoid compounds stimulate fungal growth (Nair et al, 1991;Gianinazzi-Pearson et al, 1989) and root colonization (as reported here) cannot be determined from our experiments. As indicated by others (Adesanya, O'Neill & Roberts, 1986), the effects of these compounds on fungi may result from their effects on membrane permeability, enzyme activity or DNA transcription.…”
Section: Discussionmentioning
confidence: 70%
“…Inoculations with VAM fungi can result in accumulation of isoflavonoid compounds in legumes (Morandi, Bailey, & Gianinazzi-Pearson, 1984;Morandi, 1989); but, the possible effects of these compounds on VAM colonization and plant growth have been overlooked. Formononetin and biochanin A, previously isolated and identified from clover roots (Nair et al, 1991), exhibited the highest biological activity for stimulating VA mycorrhiza formation, whereas the other flavonoids tested, including the isoflavonoid genestein, were inactive when applied at solution concentrations of 5mgr'. Although formononetin and biochanin A have been found to exhibit low antifungal activity against other soil fungi (Debnam & Smith, 1976), their VAM stimulating effects are rather unexpected since these compounds are considered as phytoalexins (Van Etten, 1976) and also as allelochemicals in clover at concentrations of 100 mg r^ or higher (Tamura et al 1969).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…No entanto, tem-se observado a ocorrência de fitotoxicidade em culturas sensíveis (carryover) plantadas após a utilização desses herbicidas, cujo efeito residual varia de alguns meses até três anos ou mais. Esse fenômeno tem sido observado para os herbicidas atrazine e imazaquin (Siqueira et al, 1991), além de outros, como tebuthiuron, fomesafen e trifloxysulfuronmetyl. Nessa situação, torna-se possível e recomendável o emprego de espécies vegetais na descontaminação dos solos.…”
Section: Exemplos De Fitorremediação De Herbicidasunclassified
“…Além disso, produtos que apresentam efeito residual longo -que pode variar de alguns meses até três anos ou mais -provocam fitotoxicidade em culturas sensíveis (carryover) plantadas após a utilização desses herbicidas, como observado para atrazine e imazaquin por Siqueira et al (1991).…”
unclassified